TRIM8 Blunts the Pro-proliferative Action of ΔNp63α in a p53 Wild-Type Background - Caratozzolo, Mariano Francesco; Marzano, Flaviana; Abbrescia, Daniela Isabel; Mastropasqua, Francesca; Petruzzella, Vittoria; Calabrò, Viola; Pesole, Graziano; Sbisà, Elisabetta; Guerrini, Luisa; Tullo, Apollonia (Frontiers in Oncology, 2019)
The p53 gene family network plays a pivotal role in the control of many biological processes and therefore the right balance between the pro-apoptotic and pro-survival isoforms is key to maintain cellular homeostasis. The stability of the p53 tumor suppressor protein and that of oncogenic ΔNp63α, is crucial to control cell proliferation. The aberrant expression of p53 tumor suppressor protein and oncogenic ΔNp63α contributes to tumorigenesis and significantly affects anticancer drug response. Recently, we demonstrated that TRIM8 increases p53 stability, potentiating its tumor suppressor activity. In this paper, we show that TRIM8 simultaneously reduces the level of the pro-proliferative ΔNp63α protein, in both a proteasomal and caspase-1 dependent way, thereby playing a critical role in the cellular response to DNA damaging agents. Moreover, we provided evidence that ΔNp63α in turn, suppresses TRIM8 gene expression by preventing p53-mediated transactivation of TRIM8, therefore suggesting the existence of a negative feedback loop. These findings indicate that TRIM8 exerts its anticancer power through a joint action that provides on one hand, the activation of the p53 tumor suppressor role, and on the other the quenching of the oncogenic ΔNp63α protein activity. The enhancement of TRIM8 activity may offer therapeutic benefits and improve the management of chemoresistant tumors.